Morphogenesis of immune formations of ducks' intestine - T. A. Mazurkevych; S. I. Usenko (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
The morphogenesis of immune formations of duck intestines was studied. Material for histological studies was taken from Blagovarsky cross broiler ducks aged from one to 420 days. The obtained sections were stained with Karatsi's hematoxylin and eosin – to establish the features of the microscopic structure of intestinal immune formations, Weigert's hematoxylin and picrofuchsin according to Van Gieson and aniline blue in combination with acid fuchsin and Orange G according to Mallory – to identify collagen fibers, resorcin-fuchsin according to Weigert – for differentiation of elastic fibers. To determine reticular fibers, sections were impregnated with 1–2 % argentum nitrate solution according to the modified Kelemen method. Electron microscopy studies were carried out to study the ultrastructure of the immune formations of the intestines of 180-day-old ducks. The studies have established that the intestinal wall in the places where immune formations of the intestines in ducks are localized is formed by tunica mucosa, tunica muscularis and tunica serosa, the area of which in all immune formations changes unevenly and asynchronously with the birds’ age. The tunica mucosa occupies the largest area, which changes unevenly and asynchronously, reaching maximum values (from 71.66 ± 0.25 to 81.28 ± 0.19 %) during the first 25 days of the ducks' life. The tunica muscularis occupies a smaller area than the tunica mucosa. It decreases unevenly in the first 25 days of a bird’s life, and in older birds it increases and reaches maximum values (35.68 ± 0.49–46.67 ± 1.39 %) in 330- and 420-day-old birds. The tunica serosa occupies the smallest area. In day-old birds, this indicator is the highest (from 2.47 ± 0.07 to 6.20 ± 0.02 %) and decreases with age by 1.24–6.52 times. Lymphoid tissue, which determines the functions of immune formations, is located in their tunica mucosa and tunica muscularis. It is detected in the tunica mucosa of all immune formations and the tunica muscularis of caecal diverticula from the bird’s one-day age, in the tunica muscularis of other immune structures – from the age of 10–20 days. The total area of lymphoid tissue increases from one day (27.03 ± 0.88–31.72 ± 0.04 %) to 150 days of age in ducks in Peyer's patches of the duodenum and jejunum and cecal diverticula (59.86 %, 59.58 ± 1.28, 65.12 ± 0.50 %), up to 210 days of age in Peyer’s patches of the ileum (71.64 ± 1.03 %), up to 330 days of age in Peyer’s patches of the cecum (37.84 ± 5.12 %), up to 420 days of age in Meckel’s diverticulum (55.24 ± 0.37 %). In older birds, the area of lymphoid tissue decreases, which indicates the beginning of its involution and, accordingly, the involution of immune formations.